Cần gấp Tìm `x,y,z` biết `3x = 4y=5z – 3z – 4y` và `2x + y = z – 38` 30/08/2021 Bởi Rylee Cần gấp Tìm `x,y,z` biết `3x = 4y=5z – 3z – 4y` và `2x + y = z – 38`
Đáp án: $(x;y;z)= (-40;-39;-72)$ Giải thích các bước giải: Ta có: $\quad 3x = 4y$ $\Leftrightarrow \dfrac x4 =\dfrac y3$ Đặt $\dfrac x4 =\dfrac y3= k$ $\Rightarrow \begin{cases}x = 4k\\y = 3k\end{cases}$ Khi đó: $\quad 4y = 5z – 3x – 4y$ $\Leftrightarrow 8y + 3x = 5z$ $\Leftrightarrow 24k + 12k = 5z$ $\Leftrightarrow z = \dfrac{36k}{5}$ Ta được: $\quad 2x + y = z – 38$ $\Leftrightarrow 8k + 3k = \dfrac{36k}{5} – 38$ $\Leftrightarrow \dfrac{19k}{5} = -38$ $\Leftrightarrow k = -10$ $\Rightarrow \begin{cases}x = 4k = -40\\y = 3k = -30\\z = \dfrac{36k}{5}= – 72\end{cases}$ Vậy $(x;y;z)= (-40;-39;-72)$ Bình luận
Ta có : `2x + y = z – 38` `⇒ 2x + y – z = -38` `+)` Vì `3x = 4y = 5z – 3x – 4y ⇒ 3x = 4y = 5z – 6x` `⇒ 3x = 5z – 6x ⇒ 9x = 5z ⇒ x/5 = z/9 ⇒ x/20 = z/36 (1)` `+)` Vì `3x = 4y ⇒ x/4 = y/3 ⇒ x/20 = y/15 (2)` Từ `(1)` và `(2)` suy ra: x/20 = y/15 = z/36` Áp dụng tính chất của dãy tỉ số bằng nhau ta có: `x/20 = y/15 = z/36 = (2x + y – z)/(40 + 15 – 36) = (-38)/19 = -2` Khi đó: `x/20 = -2 ⇔ x = -40` `y/15 = -2 ⇔ y = -30` `z/36 = -2 ⇔ z = -72` Vậy `(x; y; z) = (-40; -30; -72)` Bình luận
Đáp án:
$(x;y;z)= (-40;-39;-72)$
Giải thích các bước giải:
Ta có:
$\quad 3x = 4y$
$\Leftrightarrow \dfrac x4 =\dfrac y3$
Đặt $\dfrac x4 =\dfrac y3= k$
$\Rightarrow \begin{cases}x = 4k\\y = 3k\end{cases}$
Khi đó:
$\quad 4y = 5z – 3x – 4y$
$\Leftrightarrow 8y + 3x = 5z$
$\Leftrightarrow 24k + 12k = 5z$
$\Leftrightarrow z = \dfrac{36k}{5}$
Ta được:
$\quad 2x + y = z – 38$
$\Leftrightarrow 8k + 3k = \dfrac{36k}{5} – 38$
$\Leftrightarrow \dfrac{19k}{5} = -38$
$\Leftrightarrow k = -10$
$\Rightarrow \begin{cases}x = 4k = -40\\y = 3k = -30\\z = \dfrac{36k}{5}= – 72\end{cases}$
Vậy $(x;y;z)= (-40;-39;-72)$
Ta có : `2x + y = z – 38`
`⇒ 2x + y – z = -38`
`+)` Vì `3x = 4y = 5z – 3x – 4y ⇒ 3x = 4y = 5z – 6x`
`⇒ 3x = 5z – 6x ⇒ 9x = 5z ⇒ x/5 = z/9 ⇒ x/20 = z/36 (1)`
`+)` Vì `3x = 4y ⇒ x/4 = y/3 ⇒ x/20 = y/15 (2)`
Từ `(1)` và `(2)` suy ra: x/20 = y/15 = z/36`
Áp dụng tính chất của dãy tỉ số bằng nhau ta có:
`x/20 = y/15 = z/36 = (2x + y – z)/(40 + 15 – 36) = (-38)/19 = -2`
Khi đó: `x/20 = -2 ⇔ x = -40`
`y/15 = -2 ⇔ y = -30`
`z/36 = -2 ⇔ z = -72`
Vậy `(x; y; z) = (-40; -30; -72)`